FABRICATION OF SUPERHYDROPHOBIC LAYER ON POLYCARBONATE AS VISOR HELMET - ASTARI SIREGAR (NIM : 13310026); RACHMAT CAHYONO LASAMA (NIM : 13310095), DEVY
The applications of superhydrophobicity on the material surface has been widely applied to various purposes in recently years. In this study, we used polycarbonate helmet visor to fabricate a superhydrophobic helmet. This method involved preparation of nano SiO2 that obtained from sol-gel process of MTMS solution : MeOH : H2O mole ratio of 1 : 21.42 : 7.5 with 3 M NH4F as catalyst, followed by stearic acid deposition on a substrate of SiO2 PC using the spin coating method with various stearic acid concentration, variation size of SiO2, variation ratio between SiO2 and stearic acid solution, as well as variations in the amount of layer on the coating process. Stearic acid is used to lower the surface energy of polycarbonate, while SiO2 is used to exhibit the surface roughness. The surface characterization was performed using scanning electron microscopy, energy dispersive spectroscopy, UV-Vis spectrophotometer, and contact angle analysis using software ImageJ. The effect of silica size variation on water contact angle of polycarbonate have been investigated. With decreasing the size of the silica, the water contact angle increase up to more than 150°. Optimal results obtained through spincoating method by dissolving 0.125 grams of SiO2 into 10 ml of 3% solution of stearic acid in ethanol. This experiment exhibit maximum contact angle of 162.145º. Following the model of the surface hydrophobic properties Cassie-Baxter with CAH of 1.30o and sliding angle of 2.81o.